2017
DOI: 10.1002/aic.15728
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer performance of NETmix—A novel micro‐meso structured mixer and reactor

Abstract: NETmix is a novel static mixing technology consisting on a network of unit cells, comprising chambers interconnected by channels. To assess the heat transfer capacity of NETmix, the NUB model was implemented to perform hydrodynamics and heat transfer simulations. Due to the periodic nature of the NETmix structure, two central chambers and six half‐chambers were found to be sufficient to be representative of the whole network. The Nusselt numbers were determined based on the CFD simulations, and when compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
(68 reference statements)
0
11
0
3
Order By: Relevance
“…Previous works have shown that the geometry and the flow in NETmix obey to a repetitive pattern (visible in Figure 1) which enables to simulate only a subdomain of the full network to study the NETmix reactor (Fonte et al, 2013;Costa et al, 2017). Fonte (2013) and Fonte et al (2013) developed a 3D geometry that consisted of three full chambers interconnected to 6 half chambers, the NETmix Unit Block (NUB) shown in Figure 3 (left).…”
Section: Extendednub Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works have shown that the geometry and the flow in NETmix obey to a repetitive pattern (visible in Figure 1) which enables to simulate only a subdomain of the full network to study the NETmix reactor (Fonte et al, 2013;Costa et al, 2017). Fonte (2013) and Fonte et al (2013) developed a 3D geometry that consisted of three full chambers interconnected to 6 half chambers, the NETmix Unit Block (NUB) shown in Figure 3 (left).…”
Section: Extendednub Geometrymentioning
confidence: 99%
“…Since 2016, a photocatalytic NETmix was designed (Lima et al, 2016) which is used to perform photocatalysis studies such as kinetic modelling (Marinho et al, 2017;Santos et al, 2019;Santos et al, 2021) and ozonation (Filho et al, 2019). In 2017, a NETmix device coupled to heat exchangers was developed for the continuous production of CO 2 hydrates (Costa et al, 2017;Lopes et al, 2018;Lopes et al, 2019). The NETmix reactor has also been used for microencapsulation (Moreira et al, 2020) and Pickering emulsions (Ribeiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NetMIX is an extremely efficient device for heat transfer, particularly under chaotic regime. Through the evaluation of the specific heat transfer capacity, defined as the heat power transferred by convection per unit volume of the device and per unit temperature, using a computational fluid dynamics (CFD) model, Costa et al [ 45 ] showed that NetMIX is a few orders of magnitude more effective for heat transfer than typical stirred tanks or tubular reactors and at least one order of magnitude larger than microreactors, resulting in more compact devices. [ 45 ] Specific heat transfer rate values in the range of 10 7 –10 9 W m 3 normalK 1 were obtained in NetMIX, surpassing state‐of‐the‐art existing microdevices that present typical values in the range of 10 5 –10 8 W m 3 K 1 .…”
Section: Introductionmentioning
confidence: 99%
“…NETmix operation is based on this mixing pattern of fluid contact and separation with successive expansions and contractions from channels to the chamber, enabling a large interfacial area generation. The best design and operating conditions of NETmix reactors have been studied for single-phase flow in previous works [8,9]. Complete knowhow on the mixing of multiphase flows using NETmix technology is still being built.…”
Section: Introductionmentioning
confidence: 99%